A mini-review on ductile fracture mechanism of cracked/notched composite elements - Irandoust , Kiarash (Journal of Composites and Compounds, 2024)
This study explores the ductile fracture mechanisms of cracked and notched composite elements, focusing on their structural integrity and failure behavior under various loading conditions. Composites are increasingly utilized in engineering applications due to their high strength-to-weight ratios and tailored properties; however, understanding the fracture processes is essential for optimizing their performance and durability. We analyze the key factors influencing ductile fracture, including material composition, notch geometry, and the influence of environmental conditions. This review aims to provide insights into the critical parameters that govern ductile failure, facilitating improved predictive models for the assessment and longevity of composite structures.